Extradigital glomus tumor - A rare case report - Ashwini V Ratnakar; Manasi A Gosavi; Pratik P Bhat (Wolters Kluwer Medknow Publications, 2023)
Glomus tumor is benign vascular tumors arising from modified smooth muscle cells of the glomus bodies and accounting for 1.6% of all soft-tissue tumors. The presence of glomus tumors at sites other than fingertips is a very rare occurrence. We present a rare case of a 68-year-old male with a history of painful nodules over the interscapular region for the last 10 years which was excised and sent to our department of pathology. On gross examination, the lesion was 1 × 1 cm, nodular. Cut section was gray and brown with areas of hemorrhage seen. Histopathological examination revealed a circumscribed lesion in the dermis comprising small dilated vascular spaces surrounded by sheets and clusters of glomus cells having round-oval, bland nucleus with moderate-abundant eosinophilic cytoplasm. No areas with increased mitosis, no atypia, and no necrotic areas were seen. There was no area with ductal/mucin differentiation. Glomus tumor is very rare at extradigital sites and may be often missed clinically. However, the presence of the characteristic microscopic picture of perivascular sheets of bland, uniform glomus cells should help us arrive at the correct diagnosis and provide appropriate management to the patient.